Materials Young's Modulus Identification Using Genetic Algorithms - Santos Sales, C. D. [UNESP]; Grandinetti, F. J. [UNESP]; Castro, T. S. [UNESP]; de Souza Soares, Á. M. [UNESP] (Springer Nature, 2025)
This paper presents a novel method for determining the modulus of elasticity of materials using a non-destructive testing method based on the Genetic Algorithm method. Conventional methods for determining material properties, such as tensile tests, often require specialized, expensive equipment and are inherently destructive. In contrast, the proposed method uses optimization techniques to minimize the error between the experimental curvature of a beam and its analytical model. The method is validated against preliminary results that show a high degree of accuracy in estimating the elastic modulus, with values closely matching real material properties. This approach provides a cost-effective and efficient alternative for characterizing material properties without the need for destructive testing or specialized equipment.